Nephrogenic Diabetes Insipidus (NDI): a Rare Presentation in Early Infancy- A Case Report (Bangladesh Medical Journal, 2014)
A 30 months old boy presented with polyuria and polydipsia since 6 months of age. There was no family history of similar illness. Investigations revealed serum hyperosmolarity and normal renal function. Diagnostic findings correlated with nephrogenic diabetis insipidus (NDI) as the patient was non-responsive to vasopressin in water deprivation test. MRI of brain was normal and ultrasonogram of kidney, ureter, and urinary bladder was normal and other investigations showed no abnormality. DOI: http://dx.doi.org/10.3329/bmj.v41i1.18788 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 62-63